Importance of learning a Foreign Language - Samadova Sevar Axatovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article is discussed about Communicative Language teaching with a particular reference to the teaching and learning of English Language for ESP students . The article deals with the educational management teaching process in Higher education. It is 21 century, if you look through our environment there are no life without learning foreign language. Today we analysis about how to learn foreign language and it’s learning methods to students. Nowadays everyone should learn even a foreign language. It can open the world for your future life. If you have enough knowledge for language your horizon increases widely. But there are humans that have such kind of skills and ability.